The role of advocates in achieving justice and legal certainty for the community in Banten Province - Dika Ratu Marfu'atun; Mazdhalifah Taro; Wahyudi Wahyudi (Journal of Law Science, 2026)
Advocates hold a strategic position as law enforcers who play a role in providing legal aid, assistance, defense, and protection of the community's rights in obtaining access to justice. Amidst the com-plexity of legal issues faced by the community, the presence of advocates is crucial to bridge the gap in legal understanding, especially for community groups with economic, social, and educational limitations. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out through interviews, observations, and documentation of advocates, justice seekers, and related institutions in Banten Province. The results of the study indicate that the role of advocates in realizing justice and legal certainty in Banten Province has been carried out through legal consultation functions, litigation and non-litigation assistance, and the provision of free legal aid (pro bono). However, the implementation of this role still faces various obstacles, such as low public legal awareness, limited access to legal services in certain areas, and less than optimal synergy between advocates, the government, and legal aid institutions. Therefore, it is necessary to strengthen the role of advocates through increased professionalism, equitable distribution of legal aid services, and more effective collaboration with various parties to create a legal system that is fair, certain, and in favor of the public interest. This research is expected to provide both academic and practical contributions to strengthening the role of advocates as a pillar of justice in Banten Province